Alkaline‐earth Metal Nitrides of the Main‐Group Elements: Crystal Structures and Properties of Inverse Perovskites. Issue 10 (22nd May 2013) - Niewa, Rainer
Abstract The knowledge on alkaline‐earth metal nitrides of main‐group elements with Perovskite structures of the general composition (A3Nx)E is reviewed. Compounds with closely related crystal structures denoted as Ruddlesden‐Popper‐Series are also taken into account. In a second part, radii considerations are discussed for use in prediction of the occurrence of distorted Perovskites and hexagonal Perovskite stacking variants.